2014
DOI: 10.3329/akmmcj.v5i1.18767
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive Practice of Married Women: Experience from a Rural Community of Bangladesh

Abstract: Of the world population, 75% live in developing countries characterized by high fertility rates, high maternal and infant mortality and low life expectancy 2 . In the developing world, 1/3rd of all healthy adult women are lost due to reproductive health problem 3. Female population is about 60.26 million in Bangladesh and married women of reproductive age group constitute 51.7% of all total female population4. More than 5,00,000 women die every year due to pregnancy related complications in the developing worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In line with the results of previous studies conducted in Bangladesh and its neighbouring country Nepal, this study showed that a lack of communication and negotiation ability with the husband negatively affects informed decision-making on contraceptive use and childbearing [ 7 , 33 , 34 ]. Because of the age and power differentials between wives and husbands, often a newly married adolescent girl hesitates or refrains from talking to her husband about contraceptive methods which limits inter-spousal communication.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In line with the results of previous studies conducted in Bangladesh and its neighbouring country Nepal, this study showed that a lack of communication and negotiation ability with the husband negatively affects informed decision-making on contraceptive use and childbearing [ 7 , 33 , 34 ]. Because of the age and power differentials between wives and husbands, often a newly married adolescent girl hesitates or refrains from talking to her husband about contraceptive methods which limits inter-spousal communication.…”
Section: Discussionsupporting
confidence: 89%
“…A study conducted in Bangladesh found that the husband played an important role in making decisions regarding contraceptive use and childbearing which also supports the findings of this study [ 24 ]. Another study also showed the influence that mothers-in-law have on contraceptive use and childbearing in the decision-making process [ 32 , 33 ]. Two aspects made husbands and mothers-in-law influential in this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation